Determination of SO2 and NOx ground level concentrations from stack emissions in shell Tabangao refinery using AERMOD-air dispersion regulatory model - Amarra, Francisco B. (c2004.)
The Philippine Clean Air Act of 1999 requires the use of air dispersion modeling to determine or predict ground level concentration of pollutants from point source emissions such as refinery stacks. AERMOD is the latest and the most complex model recently developed by US-EPA and AMS. This study determined the SO2 and NOx ambient concentrations from stack emissions for September 2001 to August 2002 using AERMOD. AERMOD requires specific electronic file formats to be inputted in its AERMET and AERMAP preprocessors in order to successfully run the program, which took most of the efforts in the modeling exercise. This study provides some insights into the problems encountered in the availability and processing of various data, especially in the development of meteorological data. One of the recommendations is that for AERMOD to be applicable and relevant for application in the Philippines, adequate attention should be given to upgrade the access and quality of meteorological and terrain data especially from government agencies and other non-government sources. In this study, the pollutant concentration values, in ug/NCM were calculated in two sets of receptor grids: the large scale (500 meters x 500 meters, totalling 144 points) and the small scale (100 meters x 100 meters; totaling 900 points). The values were then plotted on UTM coordinated maps of the study area. The result show that the location of the values followed the prevailing, either northeasterly or southwesterly, wind directions. Most of the high concentration values based on 24-hour average calculations were located within the property line of the plant except for June and August where the high concentration values fell approximately 1,000 meters from the property boundaries. The allowable value for 24-hour average SO2 is 180 ug/NCM and the highest concentration occurred in July 2002 with a value of 107.9 ug/NCM located inside the refinery boundary limits. The allowable yearly average for SO2 ug/NCM and the average concentration from September 2001 to August 2002 (excluding October 2001) was at 8.618 ug/NCM. The allowable vaue for 24-hour average NOx is 150 ug/NCM and the highest average concentration occurred in February 2002 at 114.5 ug/NCM located inside the refinery boundary limits. There is no regulatory limit for yearly averages of NOx, however, the average concentration value between September 2001 and August 2002 (excluding October 2001) was 9.178 ug/NCM. All values, whether it was the highest 24-hour average for the month or yearly average, were well within the regulatory limits of the Philippine Clean Air Act.
"May 2004."
Thesis (M.S. Environmental Engineering)-University of the Philippines Diliman.
Keywords: Air -- Pollution -- Philippines -- Tabangao (Maguindanao); Acid precipitation (Meteorology) -- Philippines -- Tabangao (Maguindanao); Shells -- Refining -- Philippines -- Tabangao (Maguindanao)